The Influence of Leadership Exemplary and Compensation on Employee Performance Through Work Discipline and Employee Work Environment - A. Aminullah Alam; A. Erni Ratna Dewi (International Journal of Artificial Intelligence Research, 2022)
Performance related with organization as pioneer and inspiration as achieved of prestation by employee which effect toward attitude by subordinate. The performance appointment of discipline and environment which mediation of leader exemplary and compensation which effect in direct and indirect. These research applied to know the effect of leader exemplary and compensation toward performance by employee through discipline and environment. The research used of quantitative with sample as amount 389 respondents (Slovin formulation). Gathered of data such as questioner with Likert scale. Data analysis used SEM-PLS. The result of research to found the leader exemplary have positive and significant toward discpline and environment. The compensation toward discipline was positive and insignificant, while the compensation positive and significant toward performance. The discipline and environment have positve and significant toward performance. The leader exemplary through discipline positve and significant toward performance. The compensation through environment positive and significant toward performance.